Theoretical Principles of Using Steam-Technologies in the Preparation of the Teacher of the New Ukrainian School - Olena Budnyk (Vasyl Stefanyk Precarpathian National University, 2018)
The Urgency of the problem of STEAM-education, need for training of relevant specialists, especially teachers for using modern digital technologies in the process of teaching students, orientation of the younger generation on STEM professions are discussed in the article. The essence of the digital competence of a modern specialist, which includes a system of knowledge and skills according to the conscious, responsible and critical use of digital technologies in the process of educational and labour activity, civil or social activity is defined by the author. It is revealed that the teacher's digital competence is manifested in his/her information literacy, culture of using data, communication in the information space, the ability to create relevant digital content. Theoretical principles of the introduction of innovative technologies in the pedagogical process of the New Ukrainian school are described. The forms and methods of using STEAM-technologies in a modern educational establishment are presented. The author stresses there is a need to use various learning tools during the work with students: presentations, laboratory tutorials and simulations, discussions, and peer collaboration to support learning activity, exploration, etc.